2019
DOI: 10.1080/07853890.2018.1564360
|View full text |Cite
|
Sign up to set email alerts
|

Dietary interventions in fibromyalgia: a systematic review

Abstract: Fibromyalgia (FM) is a chronic non-degenerative disease, whose nutritional therapy seems controversial. This systematic review aimed to synthesize the knowledge about the effect of dietary interventions on patient-reported outcomes (PRO) and inflammation in patients with FM. Six electronic databases -PubMed, BioMed Central, Cochrane library, EMBASE, LILACS and ISIwere searched for clinical trials, in which a dietary intervention in patients with FM diagnosed was conducted. Quality of evidence assessment was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 35 publications
4
52
0
4
Order By: Relevance
“…While a low FODMAP diet may improve IBS symptoms (73), associated with changes to the gut microbiome (46) and intestinal gas production (74), the effect on fibromyalgia symptoms had not been previously investigated. However, some dietary interventions that have been studied in fibromyalgia are associated with clinical improvements (75). Our review also concludes a high prevalence of functional bloating and/or gas (65.4%), similar to Zanetti et al's reported prevalence of 56.5% in women with fibromyalgia (54), although in their report a "functional" classification was not specified.…”
Section: Discussionsupporting
confidence: 75%
“…While a low FODMAP diet may improve IBS symptoms (73), associated with changes to the gut microbiome (46) and intestinal gas production (74), the effect on fibromyalgia symptoms had not been previously investigated. However, some dietary interventions that have been studied in fibromyalgia are associated with clinical improvements (75). Our review also concludes a high prevalence of functional bloating and/or gas (65.4%), similar to Zanetti et al's reported prevalence of 56.5% in women with fibromyalgia (54), although in their report a "functional" classification was not specified.…”
Section: Discussionsupporting
confidence: 75%
“…Ginseng is a root that contains pharmacological compounds called ginsenosides (25) and prevented pain-like behaviors following capsaicin injection into the hindpaw (26). There is growing evidence that these individual anti-inflammatory compounds can improve aspects of chronic pain, however, these studies are limited (16,19,21,23,24,26,27) and additional studies using a combination of these compounds at physiologically relevant doses are warranted (28).…”
Section: Introductionmentioning
confidence: 99%
“…A nearly 70% German FM patients used thermal baths, 35.2% use alternative therapeutics such as homeopathy, dietary supplements, and 18.4% use introspectiveor meditation-based exercises such as yoga or Tai chi [275]. Low FODMAP was found be compellingin QOL, quality of sleep, anxiety and depression and inflammatory biomarkers in FM patients [276][277][278][279][280][281]. Cognitive behavioral therapy (CBT) interventions may slow or reverse cortical gray matter atrophy, diminishescirculating proinflammatory cytokines (IL-6, IL-8, and TNF-α level) of FM patients, pain symptoms and pain perceptions, helps FM patient having fear of pain, anxiety, depression and sleep disturbances [282][283][284][285][286][287].…”
Section: Fibromyalgiamentioning
confidence: 98%